The Practice of Ginger Writer Application to Improve Students Descriptive Text - Widiawati, Xindi; Ammade, Salasiah; Nasrullah, Nasrullah (Jurnal Pendidikan Bahasa Inggris undiksha, 2022)
Nowdays students still face problems in improving their writing skills, including grammatical arrangements, lack of known vocabulary, use of inappropriate punctuation marks and setting capital letters in sentences. The purpose of this study was to analyze the improvement of students’ writing skills and respond to use of the Ginger Writer application. The subject of this study is students in class VIII of junior high school. In this study, the researcher used a writing test to see the students’ writing ability and distributed a questionnaire consisting of 16 statements in paper form. From the results of data analysis showed that the students’ writing ability increased. This is indicated by the mean score of pre-test is 52.84 and post test is 85.4. After calculating the t-test, the researcher found that (H0) was rejected and (H1) was accepted. This means that the Ginger Writer application was able to improve the ability to write descriptive texts of students. Then the results of the questionnaire also showed that most of the students gave positive responses after learning to use the Ginger Writer application in writing descriptive text.